2021
DOI: 10.1192/bjp.2021.97
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frequent assessment of suicidal thinking on its incidence and severity: high-resolution real-time monitoring study

Abstract: Summary Researchers, clinicians and patients are increasingly using real-time monitoring methods to understand and predict suicidal thoughts and behaviours. These methods involve frequently assessing suicidal thoughts, but it is not known whether asking about suicide repeatedly is iatrogenic. We tested two questions about this approach: (a) does repeatedly assessing suicidal thinking over short periods of time increase suicidal thinking, and (b) is more frequent assessment of suicidal thinking associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 8 publications
3
25
0
Order By: Relevance
“…On this one participant said: “ My first instinct is to say, if I'm getting messages or notifications, I'm more likely to start thinking, and I'm not thinking about self-harm at all, and then I get a notification from an app that has to do with self-harm, I'm going to start thinking about self-harm” (P5) . Though research has shown that studies utilizing such prompts on suicide and self-harm through ecological momentary assessment do not increase likelihood of harm ( 39 43 ), this participant's comment highlights the importance of meeting participants where they are at and respecting their needs.…”
Section: Resultsmentioning
confidence: 92%
“…On this one participant said: “ My first instinct is to say, if I'm getting messages or notifications, I'm more likely to start thinking, and I'm not thinking about self-harm at all, and then I get a notification from an app that has to do with self-harm, I'm going to start thinking about self-harm” (P5) . Though research has shown that studies utilizing such prompts on suicide and self-harm through ecological momentary assessment do not increase likelihood of harm ( 39 43 ), this participant's comment highlights the importance of meeting participants where they are at and respecting their needs.…”
Section: Resultsmentioning
confidence: 92%
“…Multiple studies on the effects of frequently assessing suicidal thoughts and behaviors have found no effect of the assessment on suicidal thoughts and behaviors. 50,51 Two metaanalyses support the notion that the assessment of suicidal thoughts does not change suicidal thoughts or behaviors. 52,53 The current evidence suggests self-monitoring should not be considered an intervention component.…”
Section: Example Of Jitai For Suicide Preventionmentioning
confidence: 95%
“…Disclosure of suicidal ideation was instead associated with relief ( 45 ). Repeated assessment of suicidal ideation in the context of AA studies did not increase suicidal ideation either ( 46 ). However, it has been noted that digital monitoring studies of mental health outcomes pose particular ethical issues, such as whether researchers should intervene, and if so, how, if participants report suicidal ideation or self-harm (impulses) ( 42 , 47 ).…”
Section: Methods and Analysismentioning
confidence: 99%